Precocious diagnose of dental decay using laser fluorescence: Part 1 - Guillén Borda, Celso (2006)
The difficulty for lhe diagnosis of carieo lessions in temporal teelh has made lhis work improve in a closer diagnosis using the F1uorescence of!he Laser. As we know lhe most sensitive part for caries is the Oclusal surface, because of !he characleristic morphology lhat this piece presents, make lhe micro organisms and rest oí íoad to stay. Normally !he caries diagnosis on !he oclusal surface is determinated by a combination of different techniques lhat includes lhe intra oral exam wilh lhe use of an explorer and radiographies. The purpose oí lhis research is to determinate lhe efficiency oí lhe Visual and radiographics exam in lhe diagnosis oí incipient caries lesion and compare lhem wilh lhe results found wilh lhe fluorescence laser technique.